The Construction of the Concept of Self-Efficacy in the Qur’an: A Thematic Interpretation and Grounded Theory Approach: (Pembentukan Konsep Kepercayaan Diri dalam Al-Qur’an: Pendekatan Interpretasi Tematik dan Teori yang Berakar pada Data) - Raihan Syahid; Muhammad Alif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2026)
This study aims to construct a conceptual model of self-efficacy from the perspective of the Qur’an, positioning spiritual values as the foundational elements in shaping personal belief and confidence. In contrast to established Western psychological frameworkssuch as Bandura’s model, which emphasizes cognitive, social, and affective dimensionsthis research proposes a Qur’anic self-efficacy framework rooted in tawhid (monotheism), tawakkul (reliance on God), and belief in divine intervention as core components of human agency. Employing a qualitative grounded theory approach and thematic Qur’anic exegesis (tafsir maudhu‘i), the study analyzed selected Qur’anic verses through open, axial, and selective coding. The analysis identified 19 key verses that form the basis of three interconnected dimensions of Qur’anic self-efficacy: (1) Personal efficacy, which instills a transcendent belief that ease accompanies hardship (Q.S. Al-Inshirah: 5); (2) Behavioral efficacy, which links persistent effort (mujahadah) to divine guidance (Q.S. Al-‘Ankabut: 69); and (3) Spiritual efficacy, affirming that each soul is only burdened within its capacity (Q.S. Al-Baqarah: 286). The primary novelty of this research lies in the formulation of “spiritual efficacy” as a distinct dimension, absent in conventional self-efficacy theories. This contribution expands the theoretical scope of psychology by integrating spiritual-transcendental values rooted in Islamic epistemology. Furthermore, the findings offer a theoretical foundation for the development of Islamic psychology and Qur’an-based character education, presenting a comprehensive model of human self-efficacy that harmonizes reason, behavior, and faith.